2008
DOI: 10.1175/2007jamc1677.1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic LES Modeling of a Diurnal Cycle

Abstract: The diurnally varying atmospheric boundary layer observed during the Wangara (Australia) case study is simulated using the recently proposed locally averaged scale-dependent dynamic subgrid-scale (SGS) model. This tuning-free SGS model enables one to dynamically compute the Smagorinsky coefficient and the subgrid-scale Prandtl number based on the local dynamics of the resolved velocity and temperature fields. It is shown that this SGS-model-based large-eddy simulation (LES) has the ability to faithfully reprod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
71
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 69 publications
(91 reference statements)
10
71
0
Order By: Relevance
“…2 of Beyrich et al, 1997). However, the Yamada and Mellor (1975) and Basu et al (2008) numerical simulations of the boundary layer in the Wangara field experiment produced jets with wind maxima that were relatively constant throughout the night, in agreement with the Wangara observations. The simulations in those studies were conducted over flat terrain but with an imposed thermal wind.…”
Section: Analytical Solutionsupporting
confidence: 82%
See 1 more Smart Citation
“…2 of Beyrich et al, 1997). However, the Yamada and Mellor (1975) and Basu et al (2008) numerical simulations of the boundary layer in the Wangara field experiment produced jets with wind maxima that were relatively constant throughout the night, in agreement with the Wangara observations. The simulations in those studies were conducted over flat terrain but with an imposed thermal wind.…”
Section: Analytical Solutionsupporting
confidence: 82%
“…An LES of the stably stratified atmospheric boundary layer over flat terrain with imposed horizontal pressure gradient force evolving from an initial daytime dry convective state (Saiki et al, 2000) and of an atmospheric boundary layer over flat terrain evolving over the course of a full diurnal cycle with imposed horizontal pressure gradient force (Kumar et al, 2006) produced Blackadar-like inertial oscillations and associated low-level jets. An LES of a full diurnal cycle over flat terrain initialized with morning sounding data from day 33 of the Wangara field experiment and forced with observed time-dependent geostrophic wind profiles (Basu et al, 2008) closely reproduced the structure of the observed low-level jet.…”
Section: Introductionmentioning
confidence: 71%
“…The simulation of Kumar et al (2006) captured the main features of the convective and stable boundary layers, including the formation of a low-level jet at night. Similarly, Basu et al (2008) modelled the ABL for a complete day of the 1967 Wangara case study.…”
Section: Introductionmentioning
confidence: 99%
“…The potential of the LASDD SGS model was established in simulations of stably stratified boundary layers [23,24], neutrally buoyant boundary layers [25], an observed diurnal cycle [14], and radioactive scalar dispersion [26]. Overall, agreements between the LES-generated turbulence statistics and some well-established empirical formulations (e.g., the local scaling hypothesis) as well as theoretical predictions (e.g., Kolmogorov spectra) were remarkable.…”
Section: Large-eddy Simulation Codementioning
confidence: 87%
“…Following the pioneering works of Deardorff in the 1970s, the field of LES of ABL turbulence (henceforth, LES-ABL) has evolved dramatically. Researchers have simulated diverse types of ABL flows (including, buoyancy-driven, shear dominated, stably stratified, transitional, and cloud-topped boundary layers; please refer to Basu et al [14] for an abridged list of related references). Various model intercomparison studies (e.g., [15][16][17]) have identified strengths and weaknesses of different LES-SGS models, and in turn, have helped the community to develop more robust ones.…”
Section: Background On Large-eddy Simulationmentioning
confidence: 99%